Comparative study of cord blood lipid profile in relation to gestational age, birth weight, and sex - Kaur, Amandeep; Masand, Rupesh; Tomar, Balvir (Indian Journal of Child Health, 2019)
Objectives: The objective of the study was to compare the cord blood lipid levels in healthy newborns according to gestational age (GA), weight, and sex. Methods: This study included 1000 healthy term and preterm neonates after obtaining parental consent at birth. The GA was confirmed using New Ballard Score. Fenton’s growth charts were utilized to classify study subjects as appropriate for GA, small for GA, and large for GA at birth. Lipid profile was measured by enzymatic colorimetric method. Serum low-density lipoprotein-cholesterol (LDL-C) was calculated by Friedewald’s formula. Results: Preterm neonates with GA of 28–36 weeks had higher mean total cholesterol, LDL, very LDL, and triglycerides levels than term neonates in contrast to their mean high-density lipoprotein (HDL) levels which was significantly lower as compared to that of term neonates. A statistically significant decline in all lipid fractions was observed with an increase in birth weight from <1.5 kg to ?2.5 kg. Females had higher lipid fractions in comparison to male neonates; however, only the difference in HDL levels was statistically significant (p<0.001). Conclusion: Low birth weight neonates exhibit higher lipid levels at birth giving scope for future research and regular follow-up of these high-risk neonates.